Implementasi Kebijakan Penanggulangan Banjir Di Kawasan Pesisir Kabupaten Tangerang - Muhamad Hilmi Rozaldi; Muhammad Khoirul Anwar (Jurnal Media Administrasi, 2024)
This research was triggered by the lack of effectiveness in implementing flood management measures at the regional, village and community levels. Problem identification shows that the coastal area of ​​Tangerang Regency has a low risk of flooding and damage due to tidal waves, this was obtained from a preparedness study which showed a low regional resilience index, preparedness index and flood implementation capacity index. The aim of this research is to evaluate the implementation of Regional Regulation Number 7 of 2020 concerning the Implementation of Disaster Management in Flood Management in the Coastal Area of ​​Tangerang Regency. The research method used is qualitative with a descriptive approach, and data collection is carried out through observation, interviews and documentation. In its analysis, this research refers to Van Metter and Van Horn's theory which includes indicators such as policy standards and objectives, resources, inter-organizational relationships, characteristics of implementing agents, economic, social and political environmental conditions, and implementing arrangements. The research results show that policy standards and objectives have not been implemented optimally, and policy objectives do not have a significant impact according to existing regulations. BPBD Tangerang Regency is experiencing a shortage of resources, both in terms of the quality of human resources, budget and materials. Although relations between organizations are maintained, they have not yet reached optimal levels. Communication with village officials is not well informed to the community, so that synergy and cooperation with the community in Tanjung Burung and Tanjung Pasir Villages has not been fully realized, especially in the coastal areas of Tangerang Regency. There is a positive attitude of implementers towards policies, but realistic and preventive action is needed in disaster management. Economic, social and political environmental conditions do not fully support the implementation of disaster management.